HeritageBot platform for service in Cultural Heritage frames. (7th August 2018) - Ceccarelli, Marco; Cafolla, Daniele; Russo, Matteo; Carbone, Giuseppe
A service robot for Cultural Heritage frames is proposed as a novel robotic platform with a modular design for both ground locomotion and flight capability. The peculiarities of the system are discussed by performance evaluation via simulation. A prototype has been built and tested both to prove the feasibility of the proposed design and to characterize its operation performance.